Kilka słów o „Temacie petersburskim” w literaturze rosyjskiej pierwszej połowy XIX wieku - Zawichrowska, Marta (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The aim of this study is to analyze the transformation and different approaches towards “the St. Petersburgtheme” in selected works of Russian writers at the end of the first part of the 19th century. This theme is known as the St. Petersburg text. The main focus of the study is put on the evolution of the St. Petersburg text in the literary historical process and the way it is presented in the literature of particular writers of the period. Furthermore, an attempt has been made to analyze how historical events and personal experiences of the writer affected the metamorphosis of the St. Petersburg text in the author’s literary works. In this paper, we shall confine our attention to Gogol’s Petersburg tales, a series of stories connected with the city ofSt. Petersburg of the 1830s and 1840s, as well as the poetry of that period.